(untitled) (Asian Journal of Agriculture, 2024)
Abstract. Emmanuel OE, Nkiruka B-CG, Nnenna OM, Ojoko NIU, Chinenyenwa T-AA, Ada AB, Oluwakemi OI, Thankgod EK, Oscar OI, Nnabugwu UB, 2024. Impact of climate change and extension service on rice farmers’ yield in Ebonyi State, Nigeria. Asian J Agric 8: 116-123. The study examined the impact of climate change and extension service on rice farmers’ yield in Ebonyi State, Nigeria. A total of 402 rice farmers were sampled through multi-stage sampling for questionnaire administration. Primary data collected were analyzed using mean, frequency, percentage, ordinary least square multiple regression techniques, the Local Average Treatment Effect (LATE) model, and the probit model. Socio-economic characteristics show that a greater proportion of the farmers were male (51.7%), married (84.1%), and attended secondary education (47.8%). Sources of climate change information were farmer-to-farmer (100%), telephone/mobile phone (98.5%), radio (92.5%), workshop/seminars (73.4%), and television (46.8%). Temperature (P<-0.01), rainfall (P<-0.01), evaporation rate (P<-0.01), and severe windstorm (P<-0.01) influenced rice yield negatively, while relative humidity (P<0.05) and atmospheric pressure (P<0.01) had a positive influence on rice yield. The results from the LATE model, which measures the average effect of a treatment on the treated, show a decrease in rice yields of 84.1% and 96.5%. Production constraints felt by rice farmers include high cost of input materials (100%), inadequate capital (100%), high cost of labor (99.8%), poor extension access and service (99.5%), and Fulani-herdsmen conflict (76.9%). The study recommends rice farmers implement climate-smart agriculture to mitigate climate change and access farm information and/or services from experienced farmers.